(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article deals with the issues of teaching the topic «Electric current in gases», development of educational and cognitive motivation and interest in this topic, development of the ability to exercise reflection in relation to actions to solve educational and cognitive problems.